Transformasi Sosial Melalui Kebijakan Penghapusan Aset Tetap Barang Milik Pemerintah Daerah Kabupaten Banyumas - Nurohman, Nurohman; Sutikno, Chamid; Pribadi, Indah Ayu Permana; Amanda, Ariesta; Milata, Chanifia Izza (Journal of Community Development and Disaster Management, 2025)
This research examines the process of writing off unused textbook assets at SMP Negeri 4 Banyumas Library through a non-auction sales system involving a third party. The study analyzes the implementation of policies for removing textbooks due to curriculum changes that render older materials irrelevant, leading to storage issues. Key aspects reviewed include authority and responsibility, write-off procedures, reporting procedures, and sales system procedures. Using qualitative methods, data was collected through observation, interviews, and documentation. The findings reveal that the fixed asset write-off process complies with existing regulations, guided by Donald S. Van Mater's theory.